Investigation of healing effects of lemon (Citrus limonum) seeds lyophilized extracts on experimental diabetic rats. (4th March 2022) - Demir, Abdulbaki; Celik, Ismail
Abstract: In this study, the effects of lemon seed lyophilised extract (LSLE) were investigated on the diabetic rats. Groups were conducted as normal control (NC), diabetic control (DC), diabetic + 20 mg acarbose/kg bw (DAC)), diabetic + 100 mg LSLE/kg bw (DLSLE1), diabetic + 200 LSLE mg/kg bw (DLSLE2) and diabetic + 400 LSLE mg/kg bw (DLSLE4). The protective and antioxsidant effects of LSLE on experimental diabetes complications were evaluated by measuring hepatic and renal damage biomarkers (HRDBs), antioxidant defence system constituents (ADSCs), diabetes biomarkers and MDA content in tissues of diabetic rats. Glucose, HRDBs, HbA1c, lipid profile (LP) levels increased in DC compared to NC whereas these parameters of the supplementation groups showed a significant decreas compared to DC. Also, it was determined an increase MDA content and fluctuate ADSCs in the DC tissues whereas the LSLE restored the parameters towards to the NC. It can be said that LSLE is may have healings effects against diabetic complications.